Vastus Medialis Obliquus Muscle Morphology in Primary and Recurrent Lateral Patellar Instability. (29th April 2014) - Balcarek, Peter; Oberthür, Swantje; Frosch, Stephan; Schüttrumpf, Jan Philipp; Stürmer, Klaus Michael
Abstract : The morphology of the vastus medialis obliquus (VMO) muscle in the anatomical setting of an unstable patella has not been described. Therefore, the purpose of this study was to investigate the morphological parameters of the VMO muscle that delineate its importance in the maintenance of patellofemoral joint stability. Eighty-two consecutive subjects were prospectively enrolled in this study. The groups were composed of thirty patients with an acute primary patellar dislocation, thirty patients with recurrent patellar dislocation, and twenty-two controls. Groups were adjusted according to sex, age, body mass index, and physical activity. Magnetic resonance imaging was used to measure the VMO cross-sectional area, muscle-fiber angulation, and the craniocaudal extent of the muscle in relation to the patella. No significant difference was found with respect to all measured VMO parameters between primary dislocation, recurrent dislocation, and control subjects with a trend noted for only the VMO cross-sectional area and the VMO muscle-fiber angulation. This finding is notable in that atrophy of the VMO has often been suggested to play an important role in the pathophysiology of an unstable patellofemoral joint.